Are mRNA based transcriptomic signatures ready for diagnosing tuberculosis in the clinic?: a review of evidence and the technological landscape - Hamada, Yohhei; Penn-Nicholson, Adam; Krishnan, Sriram; Cirillo, Daniela Maria; Matteelli, Alberto; Wyss, Romain; Denkinger, Claudia M.; Rangaka, Molebogeng X.; Ruhwald, Morten; Schumacher, Samuel G. (EBioMedicine, 2022)
Advances in discovery and validation of diagnostic, prognostic and treatment-monitoring transcriptomic signatures of tuberculosis (TB) disease could accelerate the goal to end TB. We conducted a review to evaluate whether mRNA transcriptomics technologies are sufficiently mature to develop accurate next-generation TB diagnostic tests. Early studies tended to be limited in sample size, diversity of population groups, sample collection and processing methods, while recent prospective studies have addressed these limitations. Some of the existing signatures could be used for triage; however, high cost and complexity could limit their use. For a confirmatory test, setting an optimal cut-off to maintain specificity across populations and settings is a challenge. mRNA signatures have shown the potential to quantitatively monitor response to treatment. No prognostic signatures can accurately predict progression to active TB over 2 years while short term prediction is possible. The management strategy should be defined for individuals with positive prognostic tests. - Funding - Development of this manuscript was supported by funding received from the Stop TB Partnership and USAID for the New Diagnostics Working Group. The funders had no role in paper design, article selection and review, interpretation, or writing of the paper.